Digital Transformation: A Qualitative Study on the Impact of Artificial Intelligence (AI)-Based Learning Media on Accounting Learning Motivation of Gen Z Students in Vocational High Schools - Fitriantinah, Fitriantinah (Jurnal Indonesia Sosial Sains, 2026)
Generation Z students, as digital natives, possess unique learning characteristics that are heavily reliant on technology. However, accounting is often perceived as a rigid and monotonous subject in vocational education. The integration of Artificial Intelligence (AI) into learning media offers a new level of personalization and interactivity that has the potential to reshape student motivation. This research employs a descriptive qualitative approach. Data were collected through in-depth interviews and classroom observations. The data analysis followed the Miles and Huberman model, facilitated by ATLAS.ti software to ensure systematic coding and network analysis. The results indicate that AI-based tools enhance students' intrinsic motivation by providing instant feedback and reducing academic anxiety. AI acts as a "learning assistant" that boosts Gen Z students' self-confidence, as they perceive their skills to be more aligned with the demands of the modern accounting industry (Accounting 4.0). AI-based learning media effectively enhance Gen Z students' learning motivation by functioning as an adaptive "learning assistant" that provides personalized, instant feedback and reduces psychological barriers. The integration of AI in vocational accounting education is recommended not as a substitute for teachers, but as an instructional partner to create more engaging and relevant learning experiences for the digital generation.